Wettability improved polishing pad and method for producing same
The water-repellent cushion layer in the polishing pad addresses moisture absorption issues, ensuring uniform polishing and reducing defects in semiconductor manufacturing by maintaining consistent compressibility and adhesive strength.
Patent Information
- Application Number
- JP2023066745
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-18
- Filing Date
- 2023-04-14
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-04-14
AI Technical Summary
CMP polishing pads experience moisture absorption issues in the cushion layer, leading to uneven polishing, reduced adhesive strength, and increased compressibility differences, which result in non-uniform polishing and potential separation of the polishing layer during extended use.
A polishing pad with a cushion layer having a water-repellent property, achieved by incorporating a base layer impregnated with a fluororesin or silane resin, reduces moisture absorption and maintains consistent compressibility, thereby enhancing polishing uniformity and adhesive strength.
The water-repellent cushion layer minimizes moisture absorption, maintains uniform polishing rates, reduces defects, and improves the quality of semiconductor wafers by ensuring consistent polishing performance over time.
Smart Images

Figure 0007603097000027 
Figure 0007603097000028 
Figure 0007603097000029
Abstract
Description
[Technical field]
[0001] The embodiment relates to a polishing pad for use in the chemical mechanical planarization (CMP) process of semiconductors and a method for manufacturing the same. [Background technology]
[0002] CMP polishing pads are essential materials that play an important role in the chemical mechanical planarization (CMP) process in semiconductor manufacturing, and play an important role in realizing CMP performance. During the CMP process, the CMP polishing pads remove unnecessary parts on the wafer through uniform polishing to make the wafer surface flat.
[0003] Mechanical polishing in the CMP process is performed by bringing the silicon wafer into contact with an abrasive layer having a certain surface roughness and moving them relative to each other to generate friction, while chemical polishing is performed by introducing a slurry containing a chemical abrasive between the polishing pad and the wafer to cause a reaction between the wafer surface and the slurry.
[0004] In this case, the CMP polishing pad has a laminated structure of a polishing layer, an adhesive layer, and a cushion layer, and in order to prevent deterioration of the polishing quality due to surface hardening of the polishing layer, the CMP polishing pad must always be kept wet with distilled water or slurry during polishing.
[0005] However, during the polishing process, the distilled water or slurry may be absorbed by the polishing pad, especially the cushion layer, at a portion of the side or upper surface of the polishing pad. A polishing pad with a locally reduced compressibility due to moisture absorption of the cushion layer may apply a greater pressure to the wafer during the CMP process, resulting in an uneven polishing rate of the wafer and a decrease in quality. In particular, when the polishing pad is used for a long time, the moisture absorption phenomenon of the cushion layer worsens, the volume of the edge increases compared to the center, and the compressibility significantly decreases, so that the difference in polishing rate between the center and edge becomes large during wafer polishing, making it difficult to obtain a uniform polishing layer.
[0006] Furthermore, the absorption of moisture from the cushion layer can weaken the adhesive strength between the cushion layer and the polishing layer during the CMP process, causing the edge portions to float. In severe cases, the polishing layer can be partially separated and move away from the polishing process position.
[0007] To solve this problem, conventional methods have been used, such as heat sealing the corners of the subpad (Patent Document 1) or coating the edges of the polishing pad with a waterproof substance (Patent Document 2). However, even these methods have limitations in that they cannot improve the problems of local changes in compression rate due to moisture absorption from the surface, differences in polishing speed over long-term use, and weakening of adhesive strength. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent No. 10-1890331 [Patent Document 2] Korean Patent No. 10-0785604 Summary of the Invention [Problem to be solved by the invention]
[0009] In order to solve the above-mentioned problems, the present invention aims to provide a polishing pad and a manufacturing method thereof that can improve the waterproof or water repellency of the cushion layer and prevent moisture absorption that may occur during the CMP process through the following implementation examples. [Means for solving the problem]
[0010] According to one embodiment, a polishing pad is provided that includes a laminate of a polishing layer, an adhesive layer, and a cushioning layer, the cushioning layer being water repellent and having an absorbency of 100% or less.
[0011] According to another embodiment, a method for manufacturing a polishing pad is provided, the method including the steps of manufacturing a cushion layer, applying an adhesive to the back surface of the polishing surface of the polishing layer and one side of the cushion layer, and adhering the back surface of the polishing surface of the polishing layer and one side of the cushion layer under high temperature and pressure, wherein the cushion layer has an absorption rate of 100% or less. Effect of the Invention
[0012] The polishing pad according to the above embodiment can improve the waterproof or water repellency of the cushion layer, reduce the absorption rate on the side or top surface that may occur during the CMP process, and improve the yield of wafer polishing.
[0013] Specifically, the polishing pad can minimize local changes in compression rate by imparting water repellency to the cushion layer itself, and can reduce changes in compression rate of the polishing pad even after a long period of polishing process by imparting water repellency to the cushion layer itself, thereby improving the uniformity of the polishing rate, the flatness of the wafer, and the production yield.
[0014] In addition, the volume change of the cushion layer due to moisture absorption is reduced, thereby preventing weakening of the adhesive strength of the adhesive layer and preventing the floating phenomenon between the cushion layer and the polishing layer, thereby further improving the efficiency of the wafer manufacturing process, thereby providing industrial advantages.
[0015] Therefore, by using a polishing pad according to the embodiment, the occurrence of defects on a wafer such as scratches can be reduced, polishing unevenness can be suppressed, polishing precision can be improved, and high-quality semiconductor materials can be provided. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 shows a schematic diagram of a semiconductor device manufacturing process according to one embodiment. [Diagram 2] FIG. 2 shows a layered structure of a polishing pad in which a substrate layer includes a surface coating layer according to one embodiment. [Diagram 3] FIG. 3 shows a layered structure of a polishing pad impregnated with a substrate layer according to one implementation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below with reference to the accompanying drawings, in order to enable a person skilled in the art to easily carry out the present invention. However, the present invention may be implemented in various different forms and is not limited to the implementations described in the present specification.
[0018] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0019] In the following description of implementation examples, when a layer, hole, window, region, etc. is described as being formed "on" or "under" a layer, hole, window, region, etc., "on" and "under" include all layers, holes, windows, regions, etc. that are formed "directly" or "indirectly through other components."
[0020] In addition, the criteria for the top and bottom of each component will be described based on the drawings. The size of each component in the drawings may be exaggerated for the purpose of explanation and does not represent the size actually applied.
[0021] [Polishing pad] The polishing pad according to one implementation includes a laminate of a polishing layer, an adhesive layer, and a cushioning layer.
[0022] <Cushion layer> The cushion layer supports the polishing layer and absorbs and disperses impacts applied to the polishing layer.
[0023] The cushion layer is a cushion layer with improved wetting characteristics, the cushion layer including a substrate layer, and in one embodiment of the present invention, the substrate layer may include a surface coating layer to improve the wetting characteristics of the cushion layer.
[0024] In one embodiment of the present invention, the substrate layer may be impregnated with a water-repellent resin to improve wetting properties.
[0025] In one embodiment of the present invention, the substrate layer may be a nonwoven fabric or a porous pad formed containing one or more resins selected from the group consisting of polyester resin, polyamide resin, polyurethane resin, polyolefin resin, and fluoropolymer resin.
[0026] The method for obtaining the substrate layer of the present invention is not particularly limited, but may be one obtained by single component spinning, sea-island composite spinning, or split composite spinning, etc. In addition, long-fiber nonwoven fabrics formed directly from spinning such as spunbond or meltblown, nonwoven fabrics obtained by a papermaking method, nanofibers attached to a support by spraying, dipping or coating, woven or knitted fabrics, etc. may be used, and long-fiber nonwoven fabrics obtained by a spunbond method are preferred in terms of the tensile strength of the sheet-like product, production costs, etc.
[0027] From the viewpoint of densification, the long-fiber nonwoven fabric is preferably shrunk or densified by dry heat, wet heat, or both.
[0028] The base layer may include voids. The voids included in the base layer may have an open cell structure. The porosity of the base layer may be greater than the porosity of the polishing layer.
[0029] The thickness of the base layer may be 0.5 mm to 2.5 mm. For example, the thickness of the base layer may be 0.7 mm to 2.3 mm, 0.8 mm to 2.0 mm, 1.0 mm to 1.6 mm, 1.1 mm to 1.5 mm, or 1.3 mm to 1.4 mm, but is not limited thereto. When the thickness of the base layer is within the above range, the cushion layer can be provided with sufficient support performance during polishing.
[0030] In one embodiment of the present invention, the cushion layer includes a substrate layer, and the substrate layer may include a surface coating layer formed from a coating composition including a fluorine-based resin or a silane-based resin, and the substrate layer may be impregnated with an impregnation composition including a fluorine-based resin or a silane-based resin.
[0031] The coating composition or impregnation composition may be formed from one or more of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester-based elastomer resin, polyamide-based elastomer resin, fluorine-based resin, and silane-based resin.
[0032] The fluorine-based resin may be one or more resins selected from a group of hydrophobic resins, and may be a resin having a compound containing a hydroxyl group, an isocyanate group, an epoxy group, or an amine group at its terminal.
[0033] The fluorine-based resin may be, but is not limited to, a urethane-based prepolymer, which is a copolymer of a prepolymer composition including an isocyanate compound, an alcohol compound, and a fluorine-based compound including a fluorine-based repeating unit.
[0034] The fluorine-based compound may be a compound capable of reacting with isocyanate to introduce a fluorine-based repeating unit into the main chain of urethane.
[0035] Specifically, the fluorine-based compound may be a compound containing a fluoroalkylene group having 1 to 10 carbon atoms, an ethylene oxide group containing fluorine in a branch, and / or a fluorocarbon group having 1 to 10 carbon atoms in the molecule, and containing a hydroxyl group, an isocyanate group, an epoxy group, or an amine group at the end.
[0036] The fluorine-based compound may be a fluorine-based compound having a fluorine-based repeating unit of the following Chemical Formula 1, at least one end of which includes a hydroxyl group, an amine group, or an epoxy group.
[0037] [Chemical formula 1] JPEG0007603097000001.jpg2560In the above Chemical Formula 1, R 11 and R 12 are each independently any one selected from the group consisting of hydrogen, an alkyl group having 1 to 10 carbon atoms, and fluorine, 11 and the above R 12 At least one of the R is fluorine, and the L is an alkylene having 1 to 5 carbon atoms or -O-. 13 and R 14 are each independently any one selected from the group consisting of hydrogen, an alkyl group having 1 to 10 carbon atoms, and fluorine, 13 and the above R 14 At least one of the n is fluorine. Furthermore, the n is an integer of 0 to 20, the m is an integer of 0 to 20, and both the n and the m are not 0 (zero).
[0038] Specifically, in the above Chemical Formula 1, the R 11 and R 12 are each independently any one selected from the group consisting of hydrogen, an alkyl group having 1 to 5 carbon atoms, and fluorine, 11 and the above R 12 At least one of the R is fluorine, and the L is an alkylene having 1 to 5 carbon atoms or -O-. 13 and R 14 are each independently any one selected from the group consisting of hydrogen, an alkyl group having 1 to 5 carbon atoms, and fluorine, 13 and the above R 14 At least one of the n is fluorine. The n is an integer of 0 to 10, the m is an integer of 0 to 10, and both n and m are not 0 at the same time.
[0039] The fluorine-based compound may be a compound represented by the following Formula 2.
[0040] [Chemical formula 2] JPEG0007603097000002.jpg25128In the above Chemical Formula 2, R 11 and R 12 are each independently any one selected from the group consisting of hydrogen, an alkyl group having 1 to 10 carbon atoms, and fluorine, 11 and the above R 12 At least one of the above is fluorine, the above L is an alkylene having 1 to 5 carbon atoms or -O-, and the above R 13 and R 14 are each independently any one selected from the group consisting of hydrogen, an alkyl group having 1 to 10 carbon atoms, and fluorine, 13 and the above R 14 At least one of the R 21 and the above R 22are each independently -(CH2)m1- or -(CH2)m2-(OCH2CH2)m3- (wherein m1, m2, and m3 each independently represent an integer of 1 to 20), and 41 and R 42 are each independently a hydroxy group, an amine group, or an epoxy group.
[0041] The fluorine-based compound may be included in an amount of 0.1% by weight to 4.9% by weight, 2% by weight to 4% by weight, or 2.5% by weight to 3.5% by weight based on the total weight of the prepolymer composition. If the fluorine-based compound is included in an amount of less than 0.1% by weight based on the total weight of the prepolymer composition, the effect of reducing defects due to the inclusion of the fluorine-based compound is insignificant, and if the fluorine-based compound is included in an amount of more than 4.9% by weight, gelation may occur during the synthesis process, making it difficult to synthesize the material to have the intended physical properties, and the water repellency may increase beyond a required level, weakening the adhesive strength between the layers of the polishing pad, causing the layers to separate during the manufacture or use of the polishing pad, thereby reducing the performance of the polishing pad. If the fluorine-based compound is included in the amount described above, a polishing pad having excellent defect reduction effect may be provided.
[0042] The silane-based resin may be one or more resins selected from a group of hydrophobic resins, and may be preferably a resin having a compound containing a hydroxyl group, an isocyanate group, an epoxy group, or an amine group at its terminal.
[0043] The silane-based resin may be, but is not limited to, a urethane-based prepolymer, which is a copolymer of a prepolymer composition including an isocyanate compound, an alcohol compound, and a silane-based compound containing a silane-based repeating unit.
[0044] The silane-based compound may be a compound capable of reacting with isocyanate to introduce a silane-based repeating unit into the main chain of urethane.
[0045] Specifically, the silane-based compound may be a silane-based compound having a silane-based repeating unit of the following Chemical Formula 3, at least one end of which includes a hydroxyl group, an amine group, or an epoxy group.
[0046] [Chemical formula 3] JPEG0007603097000003.jpg2430In the above Chemical Formula 3, R 11 and R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n is an integer of 1 to 30.
[0047] Specifically, in the above Chemical Formula 3, the R 11 and R 12 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and the n can be an integer of 8 to 28.
[0048] The silane-based compound may be a compound represented by the following Formula 4.
[0049] [Chemical formula 4] JPEG0007603097000004.jpg2680In the above Chemical Formula 4, R 11 , R 12 , R 13 and R 14 are each independently hydrogen or an alkyl group having 1 to 10 carbon atoms, 22 is -(CH2)m1- or -(CH2)m2-(OCH2CH2)m3- (wherein m1, m2, and m3 each independently represent an integer of 1 to 20), and 31 is an alkylene group having 1 to 20 carbon atoms, 41 and R 42 are each independently a hydroxy group, an amine group, or an epoxy group, and n is an integer of 1 to 30.
[0050] The silane compound may be included in an amount of 0.1% to 4.9% by weight, 2% to 4% by weight, or 2.5% to 3.5% by weight based on the total weight of the prepolymer composition. If the silane compound is included in an amount of less than 0.1% by weight based on the total weight of the prepolymer composition, the defect reduction effect due to the inclusion of the silane compound is insignificant, and if the silane compound is included in an amount of more than 4.9% by weight, gelation may occur during the synthesis process, making it difficult to synthesize the material to have the intended physical properties, water repellency may increase beyond a required level, and the adhesive strength between the layers of the polishing pad may be weakened, causing the layers to separate during the manufacture or use of the polishing pad, thereby reducing the performance of the polishing pad. If the silane compound is included in the amount described above, a polishing pad having excellent defect reduction effect may be provided.
[0051] In the fluorine-based resin and the silane-based resin, the isocyanate compound may be any one selected from the group consisting of p-phenylene diisocyanate, 1,6-hexamethylene diisocyanate, toluene diisocyanate, 1,5-naphthalene diisocyanate, isophorone diisocyanate, 4,4-diphenylmethane diisocyanate, cyclohexylmethane diisocyanate, and combinations thereof, but is not limited thereto.
[0052] In the fluorine-based resin and the silane-based resin, the alcohol compound may include one or more polyol compounds or monomolecular alcohol compounds.
[0053] The polyol compound may be any one selected from the group consisting of polyester polyol, polyether polyol, polycarbonate polyol, polycaprolactone polyol, and combinations thereof, but is not limited thereto.
[0054] The monomolecular alcohol compound may be any one selected from the group consisting of ethylene glycol, diethylene glycol, propylene glycol, trimethylene glycol, methylpropanediol, and combinations thereof, but is not limited thereto.
[0055] When a polyurethane resin containing a fluorine-based compound or a silane-based compound is used as the coating composition, the moisture absorption rate of the cushion layer of the polishing pad is reduced, and the compressibility and compressibility change of the polishing pad are minimized even after a long-term polishing process, thereby providing a polishing pad having excellent defect reduction effect.
[0056] 2 shows a laminated structure of a polishing pad 110 according to one embodiment, in which a polishing layer 111 and a cushioning layer 113 are bonded together by an adhesive layer 112. The cushioning layer 113 also includes a base layer 114 and a surface coating layer 115, and the surface coating layer 115 is formed on the surface of the base layer.
[0057] The surface coating layer may be manufactured by a dipping method in which the cushion layer is cut into a size of the final product, immersed in a bath containing a polyurethane resin containing a fluorine-based compound or a silane-based compound, taken out, cured, and then dried.
[0058] The cushion layer produced by the dipping method has a coating on all sides, and has a structure that makes it difficult for moisture to penetrate into the inside.
[0059] In one embodiment of the present invention, the surface coating layer may be formed on one or more surfaces or the entire surface of the substrate layer.
[0060] For example, the surface coating layer may be formed on two or more surfaces including the upper surface and side surfaces of the substrate layer, or may be formed on the entire surface of the substrate layer.
[0061] In one embodiment of the present invention, the thickness of the surface coating layer may be 75 μm to 125 μm, 80 μm to 120 μm, 85 μm to 115 μm, 90 μm to 110 μm, or 95 μm to 105 μm.
[0062] The surface coating layer may have the same or different thickness on each side. For example, the thickness of the surface coating layer located on the upper side may be 80 μm to 120 μm, and the thickness of the surface coating layer located on the side may be 80 μm to 120 μm.
[0063] When the thickness of the surface coating layer is within the above range, it is possible to effectively reduce the absorption rate of the cushion layer of the polishing pad when it comes into contact with distilled water or slurry, and to minimize the compressibility and volume change of the polishing pad, thereby reducing the occurrence of defects and scratches, thereby improving the quality of the produced wafers. Also, in the case of a pad including a window, it is possible to prevent condensation on the window, thereby extending the use time of the polishing pad.
[0064] 3 shows a laminated structure of a polishing pad 110 according to one implementation. A polishing layer 111 and a cushioning layer 113 are bonded together by an adhesive layer 112, and the cushioning layer 113 includes an impregnated backing layer 116.
[0065] It is preferable to impregnate the long fiber nonwoven fabric of the base layer with a polymer elastomer mainly composed of polyurethane by impregnation before subjecting the long fiber nonwoven fabric of the base layer to ultrafine fiber processing, because the binder effect of the polymer elastomer prevents the ultrafine fibers from falling off the polishing cloth, and when exposed to the surface of the base layer, the ultrafine fibers and the polymer resin can be uniformly dispersed.
[0066] The impregnation composition used when applying the polymeric elastomer is as described above, and N,N'-dimethylformamide, dimethylsulfoxide, etc. can be preferably used as the solvent, and an aqueous emulsion can be applied. The polymeric elastomer is applied to the nonwoven fabric by immersing the nonwoven fabric in an impregnation polymer resin solution dissolved in a solvent, and then dried to substantially solidify and solidify the polymeric elastomer. In drying, the nonwoven fabric and the polymeric elastomer can be heated at a temperature that does not impair the performance of the nonwoven fabric and the polymeric elastomer.
[0067] According to another embodiment of the present invention, the cushion layer may be a substrate layer impregnated with an impregnating polymer resin, and a surface coating layer may be further formed on one or the entire surface of the substrate layer. When the surface coating layer is formed on the substrate layer impregnated with a fluorine-based resin or a silane-based resin to provide water repellency, a more excellent effect can be obtained.
[0068] <Physical properties of cushion layer> In one embodiment of the present invention, the contact angle of the cushion layer may be 76° to 90°. For example, the contact angle of the cushion layer may be, but is not limited to, 80° to 90°, 82° to 89°, 85° to 89°, 84° to 87°, 84° to 86.5°, 87° to 89°, or 87.5° to 88.5°.
[0069] When the contact angle is within the above range, the surface energy of the surface can be reduced to minimize water absorption. In addition, the change in the contact angle of the cushion layer increases the bonding strength with the adhesive used in manufacturing the pad, reducing the possibility of delamination during wafer polishing and reducing the possibility of water penetrating between the pads.
[0070] The density of the cushion layer of the present invention is 0.1 g / cm 3 ~0.6g / cm 3 , 0.3g / cm 3 ~0.5g / cm 3 , or 0.3 g / cm 3 ~0.4g / cm 3 It could be.
[0071] The cushion layer is classified into a dry cushion layer and a hygroscopic cushion layer based on whether water or slurry is contained inside the cushion layer. In this case, the hygroscopic cushion layer may be a cushion layer in a dry state immersed in a water tank containing water or slurry for 12 to 48 hours to absorb moisture, or a cushion layer in a polishing process for 12 to 48 hours to absorb moisture. For example, the hygroscopic cushion layer may be a cushion layer in a dry cushion layer immersed in a water tank containing water for 24 hours to absorb moisture, but is not limited thereto. In addition, the hygroscopic cushion layer may be a cushion layer in a dry cushion layer that is used in a polishing process for 25 hours to absorb moisture, but is not limited thereto.
[0072] The cushion layer of the present invention may have an absorbency of 100% or less as calculated by the following formula (1). For example, the absorbency of the cushion layer may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 17% or less, 15% or less, or 10% or less, but is not limited thereto.
[0073] By adjusting the absorption rate within the aforementioned range, the effect on the change in mechanical properties such as the compressibility or hardness of the cushion layer, the change in electrical properties, and / or the change in wafer polishing characteristics can be controlled as required.
[0074] JPEG0007603097000005.jpg1281 In the formula (1), W1 is the weight (g) of a test piece obtained by cutting the cushion layer into a size of 35 mm in both width and length, and W2 is the weight (g) of the test piece measured after immersing it in water for 24 hours.
[0075] The cushion layer of the present invention may have a dry compression rate according to the following formula (2) of 3% to 15%, 4% to 13%, 5% to 10%, 5% to 8%, or 5% to 6%, but is not limited thereto.
[0076] JPEG0007603097000006.jpg1184 In the formula (2), D1 and D2 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom surfaces of the test piece, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
[0077] The cushion layer of the present invention may have a moisture absorption compression rate according to the following formula (3) of 5.0% to 6.6%, 5.0% to 6.5%, 5.2% to 6.3%, 5.3% to 6.1%, 5.7% to 6.1%, or 5.3% to 5.5%, but is not limited thereto.
[0078] JPEG0007603097000007.jpg1184 In the formula (3), D3 and D4 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom of the test piece, immersing the test piece in water for 24 hours, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
[0079] The compression ratio is a value expressed as a parameter that represents the ratio of the degree of change in thickness of the cushion layer when a weak force and a strong force are applied to the cushion layer.
[0080] A polishing pad having a cushion layer with a compression ratio satisfying the above range has a supporting force capable of ensuring excellent polishing performance and can minimize scratches generated on the polished object. Specifically, in the case of a polishing pad having a cushion layer with a compression ratio outside the above range, polishing performance such as polishing rate or polishing flatness may be reduced, and scratches may be generated on the polished object, resulting in a deterioration in the quality of the polished object.
[0081] In other words, by having the compression ratio of the cushion layer satisfy the above-mentioned range, the polishing pad manufactured can not only minimize scratches generated on the polished object, but also has excellent polishing rate and polishing flatness, and is easy to planarize materials that require a high degree of surface flatness, such as silicon wafers for semiconductor devices.
[0082] The cushion layer of the present invention may have a dry compression elastic modulus of 55% or less as determined by the following formula (4), but is not limited thereto.
[0083] JPEG0007603097000008.jpg13128 In the formula (4), D1 and D2 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom surfaces of the test piece, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
[0084] The D5 is the thickness (μm) of the test piece, which is obtained by cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the upper and lower surfaces of the test piece, applying pressure with an 85 g weight for 30 seconds, applying additional pressure with an 800 g weight for an additional 3 minutes, removing the 800 g weight, and leaving the test piece for 1 minute, and then measuring the thickness (μm) of the test piece.
[0085] The cushion layer of the present invention may have a moisture absorption compressive elastic modulus according to the following formula (5) of 60% or less, 58% or less, 57% or less, 56% or less, or 55% or less, but is not limited thereto.
[0086] JPEG0007603097000009.jpg12128 In the formula (5), D3 and D4 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom of the test piece, immersing the test piece in water for 24 hours, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
[0087] The D6 is the thickness (μm) of the test piece, which is prepared by cutting the cushion layer into a size of 25 mm in both width and length, attaching adhesive tape to the top and bottom of the test piece, immersing the test piece in water for 24 hours, applying pressure with an 85 g weight for 30 seconds, applying pressure with an 800 g weight for an additional 3 minutes, removing the 800 g weight, and leaving the test piece for 1 minute, and then measuring the thickness (μm) of the test piece.
[0088] The compressive elastic modulus is a parameter value related to the degree of recovery after a strong force is applied to the cushion layer for a certain period of time.
[0089] A polishing pad having a cushion layer with a compressive elastic modulus satisfying the above range can minimize scratches on the polished object and ensure a certain level of polishing performance even after long-term use. Specifically, in the case of a polishing pad using a cushion layer with a compressive elastic modulus outside the above range, the polishing performance may be inconsistent, such as a sudden decrease in polishing performance during long-term use, and scratches may occur on the polished object, degrading the quality of the polished object.
[0090] In other words, in the case of a polishing pad in which the compressive elastic modulus of the cushion layer satisfies the above-mentioned range, the occurrence of defects such as scratches on the polished object can be minimized, the polishing performance can be maintained constant, and excellent polishing rate and polishing flatness can be obtained.
[0091] The compressibility and compressive elasticity of the cushion layer can be designed by comprehensively adjusting not only the material and composition of the cushion layer, but also the mechanical properties, physical structure, manufacturing process conditions, post-processing conditions, storage / aging conditions, etc. of the cushion layer.
[0092] The compressive elastic modulus is related to the absorbency of the cushion layer. The higher the absorbency, the more water the cushion layer can absorb, and the greater the repulsive force that attempts to return to the original state when the cushion layer is compressed, resulting in a higher compressive elastic modulus.
[0093] The cushion layer may have a compressibility change of 30% or less, or 20% or less, according to the following formula (6):
[0094] JPEG0007603097000010.jpg12128 In the formula (6), D1 and D2 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom surfaces of the test piece, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying pressure with an additional 800 g weight for 3 minutes.
[0095] D3 and D4 are the thicknesses (μm) of the test specimens obtained by cutting the cushion layer into 25 mm pieces horizontally and vertically, attaching adhesive tape to the top and bottom surfaces of the test specimens, immersing the specimens in water for 24 hours, and then applying pressure with an 85 g weight for 30 seconds, and measuring the thicknesses (μm) of the test specimens after applying additional pressure with an 800 g weight for 3 minutes.
[0096] When the change in compressibility satisfies the above range, the impact applied to the polishing layer within a preferred range during polishing is transmitted to the cushion layer, and the physical energy of the polishing layer itself is high, improving the polishing rate and polishing uniformity. By stacking the cushion layer and the polishing layer, the desired polishing performance can be achieved, and the polishing performance can be maintained constant even after polishing for a certain period of time.
[0097] If the thickness is outside the above range, the amount of energy transmitted to the cushion layer increases, but since the cushion layer has many non-uniform pores, it is unable to absorb the energy uniformly, which may result in non-uniform flatness of the polished surface and a low polishing rate.
[0098] <Polishing layer> The polishing layer can be made from a polishing layer composition that includes a first urethane-based prepolymer, a curing agent, and a foaming agent.
[0099] A prepolymer generally refers to a polymer having a relatively low molecular weight in which the degree of polymerization has been stopped at an intermediate stage to facilitate shaping of the final product.
[0100] The prepolymer may be molded by itself or after reacting with other polymerizable compounds. Specifically, the first urethane-based prepolymer is prepared by reacting an isocyanate compound with a polyol, and may contain unreacted isocyanate groups (NCO).
[0101] The curing agent may be one or more of an amine compound and an alcohol compound. Specifically, the curing agent may include one or more compounds selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, and aliphatic alcohols.
[0102] The foaming agent is not particularly limited as long as it is one that is usually used for forming voids in a polishing pad.For example, the foaming agent may be one or more selected from a solid-phase foaming agent having a hollow structure, a liquid-phase foaming agent using a volatile liquid, and an inert gas.
[0103] The polishing layer may include pores. The pores may have a closed cell structure. The average diameter of the pores may be 5 μm to 200 μm. The polishing layer may include pores of 20 volume % to 70 volume % based on the total volume of the polishing layer. That is, the porosity of the polishing layer may be 20 volume % to 70 volume %.
[0104] The average thickness of the abrasive layer can be 0.8 mm to 5.0 mm, 1.0 mm to 4.0 mm, 1.0 mm to 3.0 mm, 1.5 mm to 2.5 mm, 1.7 mm to 2.3 mm, or 2.0 mm to 2.1 mm.
[0105] The hardness of the abrasive layer can be 40 Shore D to 80 Shore D, 50 Shore D to 80 Shore D, 40 Shore D to 70 Shore D, 50 Shore D to 70 Shore D, or 55 Shore D to 65 Shore D.
[0106] The upper surface of the polishing layer may have an uneven structure for maintaining and updating the slurry. Although the uneven structure generally has regularity, it is possible to change the groove pitch, groove width, groove depth, etc. at specific positions for maintaining and updating the slurry.
[0107] The polishing layer may include a transparent window that can be used to detect when a desired surface characteristic or thickness has been achieved and thus determine an endpoint for terminating the process.
[0108] The light beam is directed through the window onto the surface of the wafer being processed and it is reflected back through the window to a detector Based on the return signal, the wafer surface characteristics can be measured.
[0109] The window may be manufactured by forming a first through hole in the polishing layer, forming a third through hole (in any configuration) through the adhesive layer and a second through hole through the cushion layer, inserting the window into the first through hole and sealing the periphery.
[0110] <Adhesive layer> The polishing pad may include an adhesive layer disposed between the cushion layer and the polishing layer.
[0111] The adhesive layer functions to bond the polishing layer and the cushion layer to each other, and further, the adhesive layer can prevent the polishing liquid from leaking from the upper part of the polishing layer to under the cushion layer.
[0112] In addition, a portion of the adhesive layer may bond the window and the cushion layer. Specifically, a portion of the adhesive layer may be disposed between a portion of the lower surface of the window and the cushion layer. A portion of the adhesive layer may also be disposed between a portion of a side surface of the window and the cushion layer.
[0113] The polishing layer and the cushioning layer may be directly bonded to each other without the use of an adhesive layer, and the window and the cushioning layer may be directly bonded to each other without the use of an adhesive layer, or may be bonded to each other by an adhesive layer.
[0114] The adhesive layer may include a hot melt adhesive, which may be one or more types of hot melt adhesive selected from the group consisting of polyurethane resins, polyester resins, ethylene vinyl acetate resins, polyamide resins, and polyolefin resins.
[0115] The adhesive layer may have a thickness of 20 μm to 30 μm, specifically 23 μm to 27 μm.
[0116] The polishing pad may further include a double-sided tape on a lower surface of the cushion layer, which may serve to adhere the polishing pad to a platen.
[0117] [Polishing pad manufacturing method] A method for manufacturing a polishing pad according to one embodiment includes the steps of preparing a cushion layer, applying an adhesive to the back surface of the polishing surface of the polishing layer and / or one surface of the cushion layer, and adhering the back surface of the polishing surface of the polishing layer and one surface of the cushion layer under high temperature and pressure, wherein the cushion layer has an absorbency of 100% or less according to the following formula (1):
[0118] JPEG0007603097000011.jpg1282 In the formula (1), W1 is the weight (g) of a test piece obtained by cutting the cushion layer into a size of 35 mm in width and length, W2 is the weight (g) of the test piece measured after immersion in water for 24 hours.
[0119] Specifically, W1 may be the weight (g) of the cushion layer in a dry state, and W2 may be the weight (g) measured after the cushion layer is immersed in water for 24 hours.
[0120] The step of preparing the cushion layer may specifically include at least one of a method in which the cushion layer includes a substrate layer and a surface coating layer is formed on the substrate layer from a coating composition including a fluorine-based resin or a silane-based resin to prepare the cushion layer, or a method in which the substrate layer is impregnated with a resin including a fluorine-modified polyurethane resin or a silane-modified polyurethane resin to prepare the cushion layer.
[0121] The polishing layer can be prepared by using a commercially available polishing layer, or by a conventional method, which comprises sequentially or simultaneously mixing a urethane-based prepolymer, a curing agent and a foaming agent to prepare a composition, and then injecting the composition into a mold and curing it. The preparation method can further include a surface cutting and grinding step of the obtained polishing pad, a step of processing a groove on the surface, etc.
[0122] Then, a first through hole may be formed in the polishing layer by a punching process, and a second through hole may be formed in the cushion layer by a punching process.
[0123] Furthermore, when the polishing layer and the cushioning layer are bonded to each other, a first through hole of the polishing layer and a second through hole of the cushioning layer may be aligned to correspond to each other.
[0124] The polishing layer and the cushion layer are bonded to each other by a first adhesive layer disposed between the polishing layer and the cushion layer. Specifically, a first adhesive layer may be disposed on the lower surface of the polishing layer or the upper surface of the cushion layer, and the polishing layer and the cushion layer may be bonded to each other by the first adhesive layer.
[0125] The first adhesive layer may comprise a hot melt adhesive as described above, and the polishing layer and the cushioning layer may be bonded to one another by application of heat and / or pressure.
[0126] A window is inserted into the first through hole. The window may then be bonded to the cushion layer. Specifically, the window may be bonded to the cushion layer at the same time as it is inserted into the first through-hole. That is, the window may be bonded to the cushion layer by a portion of the first adhesive layer. The window may be bonded to the cushion layer by heat and / or pressure.
[0127] <Polishing pad properties> The polishing pad manufactured in this manner can suppress moisture absorption of purified water or slurry on the upper or side surface during polishing processes such as CMP, because the sub-pad of the cushion layer has excellent water repellency. Specifically, it can suppress or prevent moisture absorption of purified water or slurry on corners around the outer periphery of the cushion layer and corners of through-holes in the cushion layer used for endpoint detection.
[0128] In addition, even if slurry leakage occurs between the window and the through-hole of the polishing layer, the polishing pad can suppress moisture absorption of purified water or slurry into the cushion layer, and can prevent changes in compressibility due to wetting of the cushion layer.
[0129] The dry compression ratio of the polishing pad of the present invention may be 1.0% to 2.5%. For example, the dry compression ratio of the polishing pad may be 1.2% to 2.3%, 1.4% to 2.1%, or 1.5% to 1.9%, but is not limited thereto.
[0130] The moisture absorption compressibility of the polishing pad of the present invention may be 0.8% to 1.7%. For example, the moisture absorption compressibility of the polishing pad may be 0.9% to 1.7%, 1.0% to 1.6%, 1.1% to 1.6%, 1.1% to 1.4%, or 1.5% to 1.6%, but is not limited thereto.
[0131] A polishing pad to which a laminate having a dry compressibility and a hygroscopic compressibility satisfying the above-mentioned ranges is applied can minimize scratches generated on the polished object and have a supporting force capable of ensuring excellent polishing performance.
[0132] In one embodiment of the present invention, the polishing pad may have a compressibility change of 50% or less according to the following formula (7). For example, the polishing pad may have a compressibility change of 40% or less, 30% or less, 20% or less, or 10% or less according to the following formula (7).
[0133] JPEG0007603097000012.jpg12128 In the formula (7), P1 and P2 are the thickness (μm) of a test piece obtained by cutting the polishing pad into a size of 25 mm horizontally and vertically, and pressing the test piece with an 85 g weight for 30 seconds, and the thickness (μm) of the test piece after pressing the test piece with an 800 g weight for 3 minutes, respectively. P3 and P4 are the thickness (μm) after test pieces cut from the polishing pad to 25 mm in both width and length were immersed in a tank of water for 24 hours, and then pressed with an 85 g weight for 30 seconds and the thickness (μm) after an additional 800 g weight was applied for 3 minutes.
[0134] When the change in compressibility falls within the above-mentioned range, the amount of impact applied to the polishing layer during polishing is within a preferred range and is transmitted to the cushion layer during polishing, and the physical energy of the polishing layer itself is high, which can improve the polishing rate and polishing uniformity, resulting in excellent quality.
[0135] The interfacial adhesion of the polishing pad is measured by measuring the interfacial adhesion between each polishing layer and each cushion layer by a 180° peel strength method using a universal testing machine (UTM) device, and the interfacial adhesion may be 6.0kgf / 25mm to 7.7kgf / 25mm, 6.3kgf / 25mm to 7.7kgf / 25mm, 6.3kgf / 25mm to 7.5kgf / 25mm, 6.5kgf / 25mm to 7.5kgf / 25mm, or 6.8kgf / 25mm to 7.4kgf / 25mm.
[0136] Although the interfacial adhesion may decrease due to coating or impregnation of the cushion layer, if the interfacial adhesion falls within the above-mentioned range, it is possible to provide sufficient adhesion of the polishing pad required during the polishing process and to prevent the polishing layer from being partially separated and leaving the position of the polishing process during the polishing process.
[0137] The polishing rate of the polishing pad of the present invention can be from 2500 Å / min to 3000 Å / min.
[0138] In one embodiment of the present invention, the polishing pad may have a polishing flatness of 3.5% or less according to the following formula (8). For example, the polishing pad may have a polishing flatness of 3.0% or less, 2.5% or less, 2.4% or less, or 2.3% or less according to the following formula (8).
[0139] Equation (8): Polishing flatness (%) = (standard deviation of polished thickness (Å) / average polished thickness (Å)) × 100
[0140] When the polishing flatness of the polishing pad is within the above-mentioned range, it is easy to flatten the surface of an object to be polished that requires a high degree of surface flatness, and a semiconductor material of excellent quality can be provided.
[0141] Regarding the durability of the polishing pad of the present invention, when the polishing pad is visually observed after completing a 25-hour polishing process, no bubbles or breaks are observed on the polished surface.
[0142] The polishing pad of the present invention can reduce defects in silicon wafers produced using the polishing pad of the present invention due to the uniform transfer of energy, for example, reducing the occurrence of defects by 85% or more, 88% or more, or 92% or more.
[0143] After completing a polishing process for 25 hours using the polishing pad of the present invention, the number of defects may be 3 or less. Specifically, the number of defects may be 2 or less, 1 or less, or 0.
[0144] The polishing pad of the present invention maintains the same level of cutting rate, polishing rate, etc. as existing polishing pads and can significantly reduce the degree of defect generation, thereby significantly reducing the defective rate of silicon wafers due to defects.
[0145] (Example) The above will be described in more detail with reference to the following examples, however, the following examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.
[0146] <Manufacture of cushion layer> (Production Examples 1 to 3) The polyester fiber nonwoven fabric was impregnated with polyurethane resin (100 parts by weight of polyurethane resin consisting of 0.7 mol of polytetramethylene glycol with an average molecular weight of 3000 and 0.3 mol of aliphatic diamine per 1.0 mol of aliphatic diisocyanate, dispersed in water together with 5 parts by weight of emulsifier), then cured and dried in an oven at 130°C to produce sheets with overall thicknesses of 1.6 mm, 1.4 mm, and 1.0 mm, respectively.
[0147] (Production Examples 4 to 6) An aqueous solution containing 100 parts by weight of the polyurethane resin used in Production Example 1 and 3 parts by weight of a fluorine-based resin (Fluorolink (registered trademark) E10-H, manufactured by Solvay) was applied to one side of each of the sheets in Production Examples 1 to 3 by dipping, cured in an oven at 130°C, and then dried to form a coating layer with a thickness of 100 μm.
[0148] (Examples 7 to 9) The polyester fiber nonwoven fabric was impregnated with an aqueous solution of the polyurethane resin used in Preparation Example 1 to which 3 parts by weight of a silane-based resin (IM11, Wacker) was added, and then cured and dried in an oven at 130°C to produce sheets with overall thicknesses of 1.6 mm, 1.4 mm, and 1.0 mm, respectively.
[0149] In the above Production Examples 4 to 9, a fluorine-based resin was used for the coating layer, and a silane-based resin was used for the impregnation, but a silane-based resin may be used for the coating layer, and a fluorine-based resin may be used for the impregnation.
[0150] <Manufacture of polishing pads> Example 1 A polyurethane adhesive (YOUNGCHANG CHEMICAL, HMF27) was applied to the back side of the polishing surface of the polishing layer as a heat-sealing adhesive to a thickness of 27 μm, and the heat-sealing adhesive was applied to one side of the cushion layer of the above-mentioned Manufacturing Examples 1 to 9 to a thickness of 27 μm. Then, the back side of the polishing surface of the polishing layer was placed so as to abut against one side of the cushion layer of the above-mentioned Manufacturing Example 4, and then the polishing layer and the cushion layer were attached by pressing them at a 50% gap (Gap) of the arithmetic thickness using a pressure roller under a condition of 120°C. Then, the polishing pad was manufactured by placing it under a condition of 25°C for 24 hours and post-treating it.
[0151] (Examples 2 to 6 and Comparative Examples 1 to 3) Polishing pads were produced in the same manner as in Example 1, except that the cushion layers of Production Examples 1 to 3 and 5 to 9 were used instead of the cushion layer of Production Example 4, as shown in Table 4 below.
[0152] (Experimental Example) <Hardness> The cushion layer samples produced in Production Examples 1 to 9 were cut to 5 cm x 5 cm, and a PSA (an acrylic adhesive having an adhesive strength of 2200 gf / inch or more on both sides of a PET substrate (thickness 50 μm)) was applied to the upper and lower surfaces, and a test adhesive layer was formed using an acrylic adhesive tape with a PET liner thickness of 75 μm. After storing at a temperature of 25° C. for 12 hours, the Asker C hardness was measured using a hardness tester.
[0153] <Compressibility and compressive elasticity> For the cushion layer samples produced in Production Examples 1 to 9, test pieces measuring 25 mm in both width and length were taken from 30 mm away from the edge, and then test adhesive layers were formed on the top and bottom surfaces using an acrylic adhesive tape with an adhesive strength of 2200 gf / inch or more applied to both sides of PSA (PET base material, thickness 50 μm) and a PET liner thickness of 75 μm.
[0154] In addition, for the polishing pad samples manufactured in Examples 1 to 6 and Comparative Examples 1 to 3, test pieces with a width and length of 25 mm were taken from the edge 30 mm position to manufacture test pieces. The dial gauge of each test piece was measured in an unloaded state, and the first thickness (D1) was measured after 30 seconds of pressing with a standard weight of 85 g. After setting the pressing condition (total 885 g) by adding a weight of 800 g to the test piece pressed with the standard weight for 30 seconds, the second thickness (D2) was measured after 3 minutes. Then, the dry compression rate (%) was calculated using the following formula (2).
[0155] JPEG0007603097000013.jpg12128 In the formula (2), D1 and D2 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom surfaces of the test piece, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
[0156] Then, under the above pressure conditions, the 800 g weight was removed and the specimen was left for 1 minute, after which the third thickness (D5) was measured and the dry compression elastic modulus (%) was calculated using the following formula (4).
[0157] JPEG0007603097000014.jpg11128In the formula (4), The D5 is the thickness (μm) of the test piece, which is prepared by cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the upper and lower surfaces of the test piece, applying pressure with an 85 g weight for 30 seconds, applying additional pressure with an 800 g weight for an additional 3 minutes, removing the 800 g weight, and leaving the test piece for 1 minute, after which the thickness (μm) of the test piece is measured.
[0158] Regarding the moisture absorption compressibility and moisture absorption compressive elasticity, the test pieces were immersed in a water tank for 24 hours to allow them to fully absorb moisture, and then taken out and moisture was removed from both sides. After that, the first thickness (D3), second thickness (D4), and third thickness (D6) of each test piece were measured, and the moisture absorption compressibility and moisture absorption compressive elasticity were calculated using the following formulas (3) and (5).
[0159] JPEG0007603097000015.jpg1185 In the formula (3), D3 and D4 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom of the test piece, immersing the test piece in water for 24 hours, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
[0160] JPEG0007603097000016.jpg11128 In the formula (5), The D6 is the thickness (μm) of the test piece, which is prepared by cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the top and bottom surfaces of the test piece, immersing the test piece in water for 24 hours, applying pressure with an 85 g weight for 30 seconds, applying additional pressure with an 800 g weight for an additional 3 minutes, removing the 800 g weight, and leaving the test piece for 1 minute, after which the thickness (μm) of the test piece is measured.
[0161] <Absorption rate> For the cushion layer samples produced in Production Examples 1 to 9, the weight (W1) of a test piece measuring 35 mm in both width and length was measured, and the test piece was immersed in a water tank for 24 hours to absorb moisture sufficiently. After that, the test piece was taken out and the weight (W2) was measured, and the absorbency (%) was calculated using the following formula (1).
[0162] JPEG0007603097000017.jpg1182 In the formula (1), W1 is the weight (g) of a test piece obtained by cutting the cushion layer into a size of 35 mm in width and length, W2 is the weight (g) of the test piece measured after immersion in water for 24 hours.
[0163] <Contact angle> According to a standard test method (ASTM D 5946), a water droplet was dropped onto the surface of the cushion layer produced in Production Examples 1 to 9, and the angle between the imaginary tangent to the edge where the water droplet contacts the surface of the cushion layer and the surface of the cushion layer was measured using a contact angle measuring instrument (DST-60).
[0164] <Interfacial adhesion> The interfacial adhesion between each polishing layer and each cushion layer of each polishing pad manufactured in Examples 1 to 6 and Comparative Examples 1 to 3 was measured using a universal testing machine (UTM) by the 180° peel strength method. In this case, the test pieces were cut to a size of 25 mm x 300 mm, and the grip was held at a position with a margin of about 50 mm from each test piece, and the test speed was 300 mm / min.
[0165] The polishing conditions using the polishing pads of the Examples and Comparative Examples are as shown in Table 1 below.
[0166] [Table 1]
[0167] The polishing pads produced in Examples 1 to 6 and Comparative Examples 1 and 3 were measured and evaluated for physical properties as follows, and the results are shown in Table 4 below.
[0168] <Polishing rate> Using a CMP polishing apparatus, a PETEOS wafer was set on a platen to which the polishing pads manufactured in Examples 1 to 6 and Comparative Examples 1 to 3 were attached. Then, the polishing load was adjusted to 3.5 psi, and the platen was rotated at 93 rpm for 30 seconds while feeding TSO-12 (Advantech Korea) slurry onto the polishing pad at a rate of 190 ml / min to perform polishing. After polishing, the silicon wafer was removed from the carrier, attached to a spin dryer, washed with purified water (DIW), and then dried with air for 15 seconds. The difference in thickness of the dried silicon wafer before and after polishing was measured using a contact surface resistance measuring device (four-point probe). Then, the polishing rate was calculated using the following formula. Polishing rate (Å / min) = polished thickness of silicon wafer (Å) / polishing time (min)
[0169] <Polishing flatness> For the polishing pads manufactured in Examples 1 to 6 and Comparative Examples 1 to 3, a polishing process was carried out under the same conditions as in the above-mentioned method for measuring the polishing rate, and then the in-wafer film thickness was measured at 98 points, and the polishing flatness (WIWNU: Within Wafer Non Uniformity, %) was calculated using the following formula (8).
[0170] Equation (8): Polishing flatness (%) = (standard deviation of polished thickness (Å) / average polished thickness (Å)) × 100
[0171] <Durability> For the polishing pads manufactured in Examples 1 to 6 and Comparative Examples 1 to 3, a polishing process was carried out under the same conditions as the above-mentioned method for measuring the polishing rate, but after the polishing time was increased to 25 hours, the polishing pads after polishing were visually observed to see whether bubbles had occurred on the polishing surface and whether the polishing pad had broken.
[0172] <Number of surface defects> After performing a polishing process using the polishing pads manufactured in Examples 1 to 6 and Comparative Examples 1 to 3, residues, scratches, and chatter marks appearing on the wafer surface after polishing were measured using a defect inspection device (AIT XP+, KLA Tencor) (conditions: threshold 150, dye filter threshold 280).
[0173] Specifically, after polishing, the silicon wafer was moved to a cleaner and washed with 1% HF and purified water (DIW), 1% H2NO3, and purified water (DIW) for 10 seconds each. It was then moved to a spin dryer and washed with purified water (DIW), and then dried with nitrogen for 15 seconds. The dried silicon wafer was measured for defect changes before and after polishing using the defect inspection device.
[0174] [Table 2]
[0175] [Table 3]
[0176] As shown in Tables 2 and 3, the cushion layers of Production Examples 4 to 9 had significantly reduced absorbency (rate of weight change during absorption) and significantly reduced change in compressibility, compared to the cushion layers of Production Examples 1 to 3. In addition, the surface contact angle increases during surface coating, which can impart hydrophobic properties to the surface.
[0177] Preparations 4 to 9, which have water repellency due to surface coating or impregnation, show similar values of compressibility and compressive modulus in the dry and hygroscopic states, whereas Preparations 1 to 3, which do not have water repellency, show large changes in compressibility and compressive modulus in the dry and hygroscopic states. This is because Preparations 1 to 3 expand when they absorb moisture, making their initial thickness relatively thicker, and the thickness difference before and after compression in Preparations 1 to 3 is large.
[0178] [Table 4]
[0179] As can be seen from Table 4, the polishing pads of Examples 1 to 6 had less change in compressibility between dry and hygroscopic states compared to the polishing pads of Comparative Examples 1 to 3, and the physical energy of the polishing layer itself was higher, confirming that they had excellent polishing rates and polishing flatness.
[0180] Furthermore, after a certain period of polishing, the occurrence of bubbles on the polishing surface and the occurrence of breaks in the polishing pad are not visually observed, and the number of surface defects is significantly reduced, making it possible to provide a polishing pad having an excellent defect reduction effect. [Explanation of symbols]
[0181] 110: Polishing pad 120: Fixed plate 130: Semiconductor substrate 140: Nozzle 150: Abrasive slurry 160: Polishing head 170: Conditioner 111: Polishing layer 112: Adhesive layer 113: Cushion layer 114: Base material layer 115: Surface coating layer 116: Impregnated substrate layer
Claims
1. A laminate including a polishing layer, an adhesive layer, and a cushioning layer, The cushion layer includes a base material layer, The substrate layer includes a surface coating layer formed from a coating composition including a fluorine-based resin or a silane-based resin, or the base layer is impregnated with an impregnation composition containing the fluorine-based resin or the silane-based resin, The cushion layer has an absorbency of 100% or less according to the following formula (1): A polishing pad, wherein the interfacial adhesion between the polishing layer and the cushion layer is 6.0 kgf / 25 mm to 7.7 kgf / 25 mm: In the formula (1), W1 is the weight (g) of a test piece obtained by cutting the cushion layer into a size of 35 mm in width and length, W2 is the weight (g) of the test piece measured after immersion in water for 24 hours.
2. 2. The polishing pad of claim 1, wherein the surface coating layer has a thickness of 80 μm to 120 μm.
3. The substrate layer is a nonwoven fabric containing one or more resins selected from the group consisting of polyester resins, polyamide resins, polyurethane resins, polyolefin resins, and fluoropolymer resins, 2. The polishing pad according to claim 1, wherein the thickness of the substrate layer is from 0.5 mm to 2.5 mm.
4. 2. The polishing pad of claim 1, wherein the contact angle of the cushion layer is from 76° to 90°.
5. The polishing pad according to claim 1, wherein the cushion layer has a dry compression rate of 3% to 15% according to the following formula (2): In the formula (2), D1 and D2 are the thicknesses (μm) of the test specimens obtained by cutting the cushion layer into pieces measuring 25 mm in both width and length, attaching adhesive tape to the upper and lower surfaces of the test specimens, and then applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test specimens measured after applying additional pressure with an 800 g weight for 3 minutes.
6. The polishing pad according to claim 5, wherein the cushion layer has a dry compression elastic modulus of 55% or less according to the following formula (4): In the formula (4), The D5 is the thickness (μm) of a test piece obtained by cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the upper and lower surfaces of the test piece, applying pressure with an 85 g weight for 30 seconds, applying additional pressure for 3 minutes with an 800 g weight, removing the 800 g weight, and leaving the test piece for 1 minute, and then measuring the thickness (μm) of the test piece.
7. The polishing pad according to claim 1, wherein the cushion layer has a moisture absorption compressibility of 5.0% to 6.6% according to the following formula (3): In the formula (3), D3 and D4 are the thicknesses (μm) of the test piece measured after cutting the cushion layer into a size of 25 mm in both the horizontal and vertical directions, attaching adhesive tape to the upper and lower surfaces of the test piece, immersing the test piece in water for 24 hours, and applying pressure with an 85 g weight for 30 seconds, and the thicknesses (μm) of the test piece measured after applying additional pressure with an 800 g weight for 3 minutes.
8. The polishing pad according to claim 7, wherein the cushion layer has a moisture absorption compressive elasticity modulus of 60% or less according to the following formula (5): In the formula (5), The D6 is the thickness (μm) of a test piece obtained by cutting the cushion layer into a size of 25 mm in both width and length, attaching adhesive tape to the upper and lower surfaces of the test piece, immersing the test piece in water for 24 hours, applying pressure with an 85 g weight for 30 seconds, applying additional pressure for 3 minutes by adding an 800 g weight, removing the 800 g weight, and leaving the test piece for 1 minute, and then measuring the thickness (μm) of the test piece.
9. 2. The polishing pad according to claim 1, wherein the polishing flatness of the polishing pad is 3.5% or less after rotating the polishing pad at 93 rpm for 30 seconds while supplying a slurry at a rate of 190 ml / min with a polishing load of 3.5 psi against a PETEOS wafer.
Citation Information
Patent Citations
Polishing pad and manufacturing method thereof
JP2004311722A
Polishing pad
JP2009018374A
Hot-melt adhesive sheet for laminated polishing pad and adhesive-layer-bearing support layer for laminated polishing pad
JP2012232404A
Polishing pad
JP2019069498A
Polishing pad
JP2020049639A
